Analyzes of Fishery Sector Contribution on the Central Java Economic Structure - Adhyaksa Dault; Abdul Kohar; Agus Suherman (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2009)
The research objective was to analyze the fishery sector contribution on the Central Java economic structure, establishment of input and output, intermediate demand dand final demand. The method used was input output analyses using Input Output Table based on the producer price of Central Java Year 2007 which was an updating data with production sector of 19 sectors. The use of Input Output Table was to find out the contribution of fishery sector on the Central java monetary through the establishment of Input and Output. The input establishment consisted of number of intermediate input and gross domestic product, while output establishment consisted of total intermediate output and total consumption. The analyses results showed that fishery sector has a small contribution on the Central Java monetary with total input Rp 9,756.09 million or 0.07%of the total input Rp 13,443,794.31 million, whereas for total output was Rp 15,287,649.78 million. Therefore, the output establishment from the fishery sector which was used as an input for other sector was still low and will influence the small contribution of the fishery sector on the establishment of gross domestic product of Central Java  Key words: Fishery sector, role, input output, Economic